The Use of the Dialogic Teaching Approach to Promote Communicative Competencies with a Group of Intermediate English Adult Students - Pérez Segura, Kenneth Andrés (2022)
This essay intends to explore how the use of the Dialogic Teaching Approach enables my intermediate English adult students to acquire communicative competencies in a globalized society. Many Costa Ricans have been moved to learn a foreign language for monetary reasons; however, their intentions should go beyond that. Through dialogue, students can holistically learn communicative competencies to interact as social agents in different globalized communities. They are invited to embrace diversity, debate their personal conflicts, find solutions, and overall, create a better world. I conclude that, through dialectical methods, students can find a democratic space to decolonize the English language from globalization, make their voices heard, and make meaning in their daily life activities.